Applicability of the shared services concept in Zimbabwe: a case study of Old Mutual Zimbabwe Plc Ltd. - Mangoro, Gaylord T. (2017)
Due to increased competition, the dynamic business environment and pressure by shareholders to increase their wealth management have been looking at tools of attaining this. One tool that has been adopted by most businesses globally of late is the SSC. This dissertation looks to test the applicability of this concept in relation to the Zimbabwean environment. The research was broken down into five chapters as a means to try and generate the answer to the research objective. Chapter 1 was the introduction to the research and its main emphasis was to explicitly show the research gap by analysing literature of other scholars in relation to the researcher’s perceived problem. Even though most scholars agree to the notion that the SSC is a success story they are however some which are in disagreement notably Longwood and Harris (2007). However none of the literature as shown in the conceptual framework tests the applicability of the concept in different environments. After noticing this research gap based the researcher decided to test the SSC applicability in the Zimbabwean environment using OM as a case study. To enable the efficient carrying out of the research the chapter laid out the research objectives; limitations; delimitations and the underlying assumptions. Chapter 2 focused on the comprehensive literature review of the concept focusing mainly on its journey and objectives. This chapter also gave the background of the SSC and its important pillars for instance the governance framework and the SMF according to Accenture (2014). Some of the key literature findings of this chapter are that the SSC is still a new concept (Beaman, 2007 and Deloitte, Hit the road, 2011) and that cost savings is its major benefit (Deloitte, Global shared services survey, 2011 and PwC, 2012). Another key finding was that performance evaluation is a key to the effective and efficient operation of SSCs (Accenture, 2011 and PwC 2012). Chapter 3 looked at the research methodology. Methodology entails the research design and strategy to assist in the attainment of the research objectives laid out in chapter 1. It also reviewed the adopted philosophical framework, that is, the pragmatism philosophy. It is based on this philosophy the research was designed and planned. The philosophy advocates for the use of the mixed method approach which the researcher adopted. The chapter reviewed the survey (questionnaires) and interview (structured) research tools which were the primary data collection tools. The chapter also laid out the target sample and the data analysis and presentation plan. Chapter 4looked at the actual presentation and analysis of data. Before this it looked at the analysis of the response rate which was rather high and demographics characteristics of the respondents. The key findings made by the researcher based on the research results were that; the overall performance of the SSC was above average as all the research objectives were met partially of in full; all the respondents agreed with most scholars that the major benefit of the SSC w as cost savings; according the respondents the most common complaint from the clients was that of bureaucracy and; there was a discord between management and employees on the carrying out of customer surveys which raises questions about the value the SSC places on its client’s thoughts. Chapter 5 chapter looked at the overall analysis of the research. From this recommendations and conclusions to the research were extracted. One of the key recommendations was to communicate customer survey across the whole group. The conclusion generated was that indeed the SSC leads to increased efficiency, cost savings, improved customer service and value generation relative to the Zimbabwean environment.